2002
DOI: 10.1097/00005392-200202000-00059
|View full text |Cite
|
Sign up to set email alerts
|

A Family Study and the Natural History of Prenatally Detected Unilateral Multicystic Dysplastic Kidney

Abstract: Multicystic dysplastic kidney can be familial but is most commonly a sporadic anomaly. Formal screening of relatives is not recommended. Followup data on a cohort of children with prenatally detected multicystic dysplastic kidney add further support to conservative management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 10 publications
1
35
1
1
Order By: Relevance
“…The marked clinical variability found within families and between patients with identical mutations in both structural lesions and clinical outcomes is similar to that found in patients with WT-1 gene mutations (37). This may suggest that PAX2 is a spatially and temporally important regulator of renal development and that unilateral renal agenesis in affected patients may be caused by ureteric obstruction during early nephrogenesis, leading to involution of the affected kidney in utero (27,38).…”
Section: Discussionsupporting
confidence: 52%
“…The marked clinical variability found within families and between patients with identical mutations in both structural lesions and clinical outcomes is similar to that found in patients with WT-1 gene mutations (37). This may suggest that PAX2 is a spatially and temporally important regulator of renal development and that unilateral renal agenesis in affected patients may be caused by ureteric obstruction during early nephrogenesis, leading to involution of the affected kidney in utero (27,38).…”
Section: Discussionsupporting
confidence: 52%
“…Indeed, serial ultrasonography before and after birth demonstrates that MCDK can enlarge and then involute to an "aplastic" phenotype (25). Hiroaka et al (26) described a similar tendency to involute in patients born with small noncystic kidneys that had minimal function as assessed by 99m Technetium-dimercaptosuccinic acid renograms; these organs were presumably dysplastic, although histology was unavailable.…”
Section: Rd Is a Dynamic Disordermentioning
confidence: 99%
“…Sometimes, these families have multiorgan syndromes, discussed below; in other cases, the anomaly is restricted to CAKUT. MCDK can occasionally be familial (25,50), and kindreds are reported in which some individuals have renal aplasia, or "absent kidneys," whereas others have large dysplastic organs (51,52); some of this phenotypic heterogeneity might be explained by the tendency of RD toward involution. Nishimura et al (41) reported an association with a polymorphism of AT2 in US and European patients with diverse urinary tract malformations, including MCDK.…”
Section: Genetics Of Human Rdmentioning
confidence: 99%
“…Approximately 1000 UK children have end-stage renal failure, and in approximately half of these individuals, the cause is a congenital abnormality of both kidneys (2), usually renal dysplasia, in which kidneys begin to form but contain undifferentiated and metaplastic tissues, sometimes with cysts (3). Some such organs spontaneously involute to give an aplastic phenotype (4,5), and therefore a spectrum of anomalies is recognized, called renal "adysplasia" (6,7). Severe bilateral renal adysplasia occurs in approximately one in 10,000 births (3).…”
mentioning
confidence: 99%